2021
DOI: 10.3390/ijms22094787
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanosized Substances Cause Different Autophagy-Related Responses

Abstract: With rapid industrialization, humans produce an increasing number of products. The composition of these products is usually decomposed. However, some substances are not easily broken down and gradually become environmental pollutants. In addition, these substances may cause bioaccumulation, since the substances can be fragmented into micro- and nanoparticles. These particles or their interactions with other toxic matter circulate in humans via the food chain or air. Whether these micro- and nanoparticles inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 285 publications
(305 reference statements)
0
5
0
Order By: Relevance
“…Autophagy can be one of the main mechanisms of cell survival that ensures the elimination of damaged organs and biomolecules, under the action of oxidative stress induced by NPs [59]. However, if the stress factor is applied for a longer period, dysfunctions occur in various organs, and autophagy serves as a cell death mechanism, promoting the self-destruction of cells [60]. However, the dual role of autophagy in both cell survival and programmed cell death, as well as the relationship between p53 protein activity and LC3 regulation, differs in a cell type dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy can be one of the main mechanisms of cell survival that ensures the elimination of damaged organs and biomolecules, under the action of oxidative stress induced by NPs [59]. However, if the stress factor is applied for a longer period, dysfunctions occur in various organs, and autophagy serves as a cell death mechanism, promoting the self-destruction of cells [60]. However, the dual role of autophagy in both cell survival and programmed cell death, as well as the relationship between p53 protein activity and LC3 regulation, differs in a cell type dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a vital role in cellular responses against NMs and nPs exposure [ 78 ]. Whether it promotes survival or death largely depends on the type of NP or nP and the severity and timing of exposure [ 12 ].…”
Section: Autophagic Interventions In the Uptake Of Nps Nms And Npsmentioning
confidence: 99%
“…In contrast to other NMs and nano-formulations, cells exposed to nPs majorly display stimulated autophagy [ 78 ]. Interestingly, activation of autophagy is an initial response, but autophagosomes tend to accumulate within the cells at later time points due to the accumulation of nPs in lysosomes [ 215 ] 215 , which impairs autophagy flux.…”
Section: Autophagy: Indicator For Nanomaterials Toxicitymentioning
confidence: 99%
“…Recently, studies have found the role of autophagy in renal injury caused by benzopyrene (BaP) (a common organic chemical in PM 2.5 ) and diesel particulate matter. 76 Autophagy is an important mechanism by which cells cope with intracellular or extracellular stress. During autophagy, some toxic components were degraded by autolysosomes to prevent cell damage.…”
Section: Pm25 and Renal Injurymentioning
confidence: 99%